Participatory impact pathways analysis (PIPA) - Schuetz, Tonya; Douthwaite, Boru; Álvarez, S. (2009)
This tool will assist those planning research on or interventions for small reservoirs systems to use Impact Pathways Analysis to develop a plan to better bring about desired outputs, outcomes and impacts. By helping make explicit the links between project activities or program interventions on the one hand, and partner roles and inter- relationships on the other. The likelihood of achieving greater better impacts may be improved. How the Impact Pathway Analysis was found useful in the Small Reservoirs Project is presented.